Tracing Aristotelian Friendship Dynamics in John le Carré’s Agent Running in the Field - Muhammad Taufiq Gani Putra; Adeline Grace Marianne Litaay (CV. Era Digital Nusantara, 2025)
This research discusses the types of friendship that are shown in John le Carre’s Agent Running in the Field and how the friendships impacting the lives of the main characters, Nat and Ed. The research analysis uses the theory of friendship by Aristotles discussed in Lorraine Smith Pangle’s Aristotle and the Philosophy of Friendship as the theoretical review, with thematic approach as the analysis model, exstrinsic research approach using moral approach, and qualitative research design. According to the research’'s findings, there are two types of friendships in Agent Running in the Field that fits Lorraine Smith Pangle’s interpertation of Aristotles’s theory of friendship: friendship of pleasure and friendship of virtue. As for the impact of Nat and Ed’s friendships to their lifes, Nat starts to have doubts over his government who he has served for years, and he got interrogated and scapegoated after MI6 finds Ed handing over intellegence to a Russian spy, before being coerced to either turn Ed in to prison or make him a double agent who serves Britain more. For Ed, he become less guarded, he meet Florence through Nat, who eventually become his fiance, and he is able to unkowingly escape from his fate of being imprisoned or becoming a double agent. The research’s limitation is that of the potrayal of friendship in John le Carré’s Agent Running in the Field and the impacts of friendship between Nat and Ed in John le Carré’s Agent Running in the Field on their lives. The research concludes in what are the types of friendship depicted in John le Carre’s Agent Running in the Field, and how it affecting the lives of the two friends.